Strengthening the capacity of managers in pharmaceutical services based on Primary Health Care (PHC) at different levels of the health system - Emmerick, Isabel Cristina Martins (BioMed Central, 2014)
INTRODUCTION: Distance learning methods have been widely used because of their advantages to continuing professional development processes. The Primary Health Care (PHC) is a strategy which has been implemented in order to improve the efficiency of health systems. Due to the need for access to medicines and technologies regardless of the strengthening of health systems, a new approach that better integrates both pharmaceutical services and health systems has been implemented. CASE DESCRIPTION: This is a case study which consists of describing the process of restructuring, developing and implementing the second version of the Virtual Course on Primary Health Care-based Pharmaceutical Services for managers (CVSERVFAPS-12). The main objective is to strengthen the capacity of managers in pharmaceutical services, based on PHC at different levels of the health system, in order to support the restructuring and empowering of these services and, consequently, the health systems in the American region. DISCUSSION AND EVALUATION: Many evaluation tools were applied to identify the achievement/improvement of planned competencies. The intervention proposals were collectively built and intended to be more than an academic exercise, looking forward to being implemented as a strategic intervention to promote changes in the pharmaceutical services of the American region. The main strengths identified for the second version of the course were related to the quality of the didactic material and content. Additionally, the tutors’ support was commented upon as a positive aspect. The main challenges faced in this rebuilding process related to the due dates of the activities and lectures as well as the time to capture and assimilate the content. CONCLUSIONS: The CVSERVFAPS-Pilot was reformulated and CVSERVFAPS-12 is consistent with the issues raised in the pilot course’s evaluation in 2011, which were successfully implemented. The use of the distance learning strategy, through a virtual environment, for the application of the Virtual Course on PHC- based pharmaceutical services for managers, is appropriate and confirmed its role in public policy promotion through effective retention and distribution of health workers.